2023
DOI: 10.3390/ijms24108488
|View full text |Cite
|
Sign up to set email alerts
|

Abemaciclib, Palbociclib, and Ribociclib in Real-World Data: A Direct Comparison of First-Line Treatment for Endocrine-Receptor-Positive Metastatic Breast Cancer

Abstract: By the end of 2020, there were more than 8 million women alive who had received a breast cancer diagnosis in the previous 5 years, making it the most prevalent neoplasia in the world. About 70% of breast-cancer cases present positivity for estrogen and/or progesterone receptors and a lack of HER-2 overexpression. Endocrine therapy has traditionally been the standard of care for ER-positive and HER-2-negative metastatic breast cancer. In the last 8 years, the advent of CDK4/6 inhibitors has shown that adding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 41 publications
0
8
0
3
Order By: Relevance
“…In the MARIA study (RWD in Italian and German patients), 12-month progression-free rates (PFRs) were 80% in patients treated with first-line P+AI. A recently published study of 206 patients evaluated the clinical benefit of palbociclib (n = 96), ribociclib (n = 54) and abemaciclib (n = 56) after 42 months of follow-up [34]. Whilst abemaciclib was associated with a significant PFS benefit in endocrine-resistant patients and those without visceral involvement, there were no other statistically significant differences among the palbociclib, ribociclib or abemaciclib groups [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the MARIA study (RWD in Italian and German patients), 12-month progression-free rates (PFRs) were 80% in patients treated with first-line P+AI. A recently published study of 206 patients evaluated the clinical benefit of palbociclib (n = 96), ribociclib (n = 54) and abemaciclib (n = 56) after 42 months of follow-up [34]. Whilst abemaciclib was associated with a significant PFS benefit in endocrine-resistant patients and those without visceral involvement, there were no other statistically significant differences among the palbociclib, ribociclib or abemaciclib groups [34].…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1). This treatment bias may be because a greater number of lesions is a poor prognostic factor, so incorporating CDK4/6i may increase disease control and bene t PFS and OS, as described in the palbociclib trials and studies (31,(33)(34)(35). Although the number of metastases seems to be an important factor in the therapeutic decision, the location was not, as no signi cant differences were found.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1). In any case, it has been described that treatment with CDK4/6i bene ts patients regardless of whether they have visceral metastases or not (16,31,33,34). In contrast, other factors such as KI-67 > 20%, tumour grade 3 and oestrogen negative receptor did not show signi cant differences between the arms (31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that abemaciclib is associated with a lower preference weight in comparison to other CDK4/6i due to adverse events, including diarrhea, abdominal pain, grade 3/4 neutropenia, tromboembolitic disease (Maculaitis et al, 2020), or acute liver injury (Beachler et al, 2021). Additionally, findings from a singular study (Cejuela et al, 2023) underscored diarrhea as a significant adverse reaction experienced by all patients, highlighting its clinical importance (Arbuckle et al, 2000). A meta-analysis regarding the risk of other side effects, such as stomatitis, demonstrated that especially palbociclib, among all CDK4/6i, could increase this risk impacting on patient adherence to the treatment (Long et al, 2021).…”
Section: Introductionmentioning
confidence: 99%